Smooth Control Action of Sliding Mode for a Class of Electro-Hydraulic Actuator - Has, Zulfatman; Rahmat, Mohd Fua'ad; Husain, Abdul Rashid; Ghazali, Rozaimi; Md Rozali, Sahazati (IEEE, 2011)
This paper presents a sliding mode control scheme to control a class of electro-hydraulic actuator system. A reaching law and varying boundary layers approaches are proposed in the scheme. The reaching law is aimed to solve the effect of chattering and minimize the reaching time. While, varying boundary layers algorithm is applied to ensure position tracking accuracy and smooth control action. The system is presented with the inclusion of friction and internal leakage in the system model. The proposed controller abilities are investigated through simulations works in Matlab Simulink environment based on the existing system parameters. The results indicate that the proposed scheme successfully reduces the reaching time, eliminates the chattering effect, improves the tracking accuracy, and results a smooth control action. In general, this improvement offers a significant contribution for accuracy in modern equipments positioning applications.